2011
DOI: 10.1016/j.ijid.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone bone penetration in patients with septic non-union of the tibia

Abstract: CFX bone penetration was poor (<15%) in the cortical compartment and satisfactory in the more vascularized cancellous bone. The T>MIC and AUC/MIC ratios suggest that CFX achieves a satisfactory pharmacokinetic exposure in cancellous bone as far as pathogens with a MIC of <0.5 are concerned. However, considering free drug concentrations, pharmacokinetic/pharmacodynamic targets may not be fully achieved in cortical bone. As antibiotic exposure can be suboptimal in the infected cortical compartment, and drug pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
2
Order By: Relevance
“…Eleven patients undergoing surgical debridement for the tibia were given 2 g IV ceftriaxone daily for a mean of 15.8 days (Garazzino et al, 2011). In this study, Garazzino et al reported AUC/ plasma ratios of 9.32 in cortical bone and of 24.1 in cancellous bone.…”
Section: Ceftriaxonementioning
confidence: 71%
“…Eleven patients undergoing surgical debridement for the tibia were given 2 g IV ceftriaxone daily for a mean of 15.8 days (Garazzino et al, 2011). In this study, Garazzino et al reported AUC/ plasma ratios of 9.32 in cortical bone and of 24.1 in cancellous bone.…”
Section: Ceftriaxonementioning
confidence: 71%
“…When reviewing the literature, in many cases, the concentrations (of various antibiotics) in cancellous bone are similar or slightly higher than in cortical bone [11]. A study, using ceftriaxone for treatment of bone infections for at least 7 days reported higher concentrations in cancellous bone than in cortical bone [25]. However, our findings of apparently higher concentration in cortical bone compared with cancellous bone are in line with findings on levofloxacin and more to the point to findings with amoxicillin, which is structurally related to ceftriaxone,[14] but because of the high variability and the higher protein binding of ceftriaxone, these data should not be overrated at that time.…”
Section: Discussionmentioning
confidence: 99%
“…The cefetamet pivoxil is a time-dependent antimicrobial agent, and it exhibited a short-lived postantibiotic effect (PAE) (Novelli et al 2000). Thus, T [ MIC is considered as the major PK/PD parameter determining the in vivo efficacy (Montesissa et al 2003;Garazzino et al 2011). Although there is a good relationship between T [ MIC and effect, no universal agreement has been reached on the length of the duration (Mouton and Punt 2011).…”
Section: Discussionmentioning
confidence: 99%